Exercise related ventilation dynamics and clinical correlates in patients with fibrotic idiopathic interstitial pneumonias - De Martino, Marina; Cobuccio, Raffaele; Bruzzese, Dario; Rea, Gaetano; Meoli, Ilernando; Stefanelli, Francesco; Canora, Angelo; Capaccio, Annalisa; Sanduzzi, Alessandro; Matarese, Alessandro; Bocchino, Marialuisa (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Assessment of exercise performance is a key component in the management of interstitial lung diseases, as its limitation may occur very early. Aim of the present study was to assess ventilation dynamics in combination with pulse-oximetry changes in 54 clinically stable patients affected by idiopathic pulmonary fibrosis or idiopathic fibrotic nonspecific interstitial pneumonia. Testing was successfully performed with the Spiropalm 6-MWT Hand-held spirometer by the majority of cases (94%). End test oxygen saturation (SpO2) values <88% were common in most of patients (76%), with a mean distance walked of 403 meters. Ventilation significantly increased due to the contribution of the tidal volume and the respiratory frequency (RF). This finding was associated with a decrease of the end of test respiratory reserve (RR), that was <20% in 9 cases (17.6%). Lung function was inversely related to the end of test RF, while a positive correlation occurred with the end of test RR and the estimated maximal voluntary ventilation (MVV). RR was also a predictive factor of declining forced vital capacity and lung diffusion capacity for carbon monoxide (DLCO) over a 6-month period. Further factors of DLCO impairment were low SpO2 and MVV. Comparison with the cardio-pulmonary exercise test (CPET) showed that the 6-MWT end of test RR was inversely related to the CPET-derived peak RF and VE/VCO2 suggesting RR as pivotal in exercise limitation assessment. Our results open challenging perspectives in an unexplored field. Future research will include management of latent respiratory failure and monitoring of disease progression and therapy response.